Induction of ankylosis in the incisor for orthodontic tooth movement in rats - Cuoghi, Osmar Aparecido; Tondelli, Pedro Marcelo; Sonoda, Celso Koogi [UNESP]; Aiello, Carlos Alberto; Mendonça, Marcos Rogério de [UNESP]; Costa, Silvano Cesar da (Wiley, 2013)
Background/Aim: The present research evaluated the induction of ankylosis and the eruption rate in rat incisors, with the aim of achieving stable anchorage for orthodontic tooth movement (OTM) of the molars. Material and methods: Fifteen male Wistar rats were used. In the Experimental group, the right superior incisor of each animal was extracted, denuded of the PDL and the dental papilla, and reimplanted. The Control group was the left superior incisors. The eruption rate was measured at 7, 10, 12, 14, and 16 days after replantation. NiTi closed springs with a 50cN release force were installed for additional 9 days, and the eruption rate was determined. Then, the rats were sacrificed, and ankylosis was examined by microscopic analysis. Differences with P < 0.01 were defined as statistically significant. Results: The eruption rates were 0 and 0.39 mm day-1 in the Experimental group and Control group, respectively. All incisors of the Experimental group showed ankylosis according to histological analysis. Conclusions: The methodology used to induce ankylosis in this study was effective for anchoring the incisors during the OTM of rat molars, eliminating the undesirable effects consequent to continuous eruption. © 2013 John Wiley & Sons A/S.
Keywords: Ankylosis; Periodontal ligament; Rats; Tooth eruption; Tooth movement; Tooth replantation